2014
DOI: 10.1002/jcb.24887
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 Inhibition Induces Cell Death via Early Impact on Mitochondrial Function

Abstract: CK2 (official acronym for casein kinase 2 or II) is a potent suppressor of apoptosis in response to diverse apoptotic stimuli —thus its molecular downregulation or activity inhibition results in potent induction of cell death. CK2 downregulation is known to impact mitochondrial apoptotic circuitry but the underlying mechanism(s) remain unclear. Utilizing prostate cancer cell lines subjected to CK2-specific inhibitors which cause loss of cell viability, we have found that CK2 inhibition in cells causes rapid ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…CellTiter 96 ® Aqueous One assay was used to assess cell viability as previously described 43 . MDA-MB 231 and PC-3 cells were seeded into 96-well plates at 1.5 and 2.5 × 10 4 cells/well, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CellTiter 96 ® Aqueous One assay was used to assess cell viability as previously described 43 . MDA-MB 231 and PC-3 cells were seeded into 96-well plates at 1.5 and 2.5 × 10 4 cells/well, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…PC-3 and MDA-MB-231 cells were collected after AHC treatments for 48 h, suspended in fresh medium, quantified, and 500 cells (MDA-MB-231) or 1000 cells (PC-3) were plated in triplicate into 35 mm cell culture dishes. After 7 days, colonies were stained with crystal violet as previously described 43 . Colonies were counted under dark field using a cubic colony counter (AO scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Survival assay against the MBM was carried out on the nauplii of brine shrimp ( Artemia salina ). For this purpose brine shrimp eggs were hatched in artificial sea water by dissolving 38 g/l of sea salt in distilled water [ 16 ]. A lamp was placed above the open side of the tank to attract the hatched shrimps towards wall of the tank.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that IFNγ regulates the expression of a subset of genes through the activation of CK2 21 22 . To investigate whether IFNγ promotes Ikaros binding through CK2, cells were treated with IFNγ in the presence of a CK2 specific inhibitor, 4,5,6,7-tetrabromobenzotriazole (TBB) 23 . CHIP analysis demonstrated that the pretreatment with TBB abrogated IFNγ-induced binding of Ikaros to the MCJ promoter ( Fig.…”
Section: Resultsmentioning
confidence: 99%